Penerapan Relaksasi Otot Progresif Terhadap Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 Di Dusun Jengglong Kabupaten Karanganyar - Padilah Putri Nur Janah; Eska Dwi Prajayanti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia. Type 2 diabetes mellitus is the most common type of diabetes mellitus, accounting for about 90% of all diabetes cases. If not treated immediately can cause damage to the eyes, kidneys, heart disease, hypertension, stroke and even cause gangrene. One of the non-pharmacological treatments is progressive muscle relaxation therapy. Objective: To determine changes in blood sugar levels in patients with type 2 diabetes mellitus before and after progressive muscle relaxation therapy. Method: Descriptive method with a case study approach to 2 respondents in Jengglong Hamlet, Karanganyar Regency. The duration of giving progressive muscle relaxation therapy to respondents was 20 minutes in the morning and evening for 7 days from 25 May 2023 to 31 May 2023. Results: The blood sugar levels of the two respondents before applying progressive muscle relaxation therapy were 243 mg/dL and 255 mh/dL. After application, blood sugar levels dropped to 167 mg/dL and 221 mg/dL. Conclusion: The application of progressive muscle relaxation is able to reduce blood sugar levels in both type 2 diabetes mellitus patients in Jengglong Hamlet, Karanganyar Regency.